Respuesta :

Answer:

Step-by-step explanation:

The expression is

x^2 - 4

This is a quadratic expression.

To find the solution, we will equate the the expression to zero. It becomes

x^2 - 4 = 0

Add 4 to the left hand side of the equation and the right hand side of the equation. It becomes.

x^2 - 4 + 4 = 0 + 4

x^2 = 4

Take square root of the right hand side of the equation and left hand side of the equation. It becomes

√x^2 = √4

x = ± 2

x = 2 or x = - 2

Answer:

b

Step-by-step explanation:

edg 2020

ACCESS MORE